Does Participative Leadership Matters in Employees’ Outcomes During COVID-19? Role of Leader Behavioral Integrity - Usman, Muhammad; Ghani, Usman; Cheng, Jin; Farid, Tahir; Iqbal, Sadaf (Frontiers in Psychology, 2021)
The corona virus disease (COVID-19) has badly affected the social, physical and emotional health of workers specifically the nurses working in the healthcare sectors. Drawing on social exchange theory, we investigated the effects of participative leadership on employees' workplace thriving and helping behaviors among frontline workers during COVID-19 pandemic. In addition, we examined the moderating role of leader’s behavioral integrity in strengthening the relationship between participative leadership, employees workplace thriving and helping behaviors. By using two wave time lagged design and data collected from 244 healthcare workers’ moderated hierarchal regression was used to test the proposed hypotheses. As hypothesized participative leadership predicted employees workplace thriving and helping behaviors. Leader’s behavioral integrity strengthened the relationship between participative leadership and employees thriving and moderated the relationship between participative leadership helping behaviors. Implications for research, theory, and practice are discussed.